(3JGQjN GdUMGHI GdQhGI Yf QShd Gddg Udi Gddg Ydjg hSdes - (3eMeO Hf MHGf Hf CMeO Hf MHGf Hf eYGP Hf eYHO GdJejej, CHh MGJe GdHSJj, hjbGd dg GHf MHGf,J (B354 (3g` s ((3Ydi Hf YHO Gddg Hf TgGH GdOjf GdNdjdi GdMfai s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf Ke EfG PGcQhf CSeGA GdUMGHg , hfbUO efge ef Qhi Yfge GdCNHGQ s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B78 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B173s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B76 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs